Clinical characteristics and genetic analysis of a Chinese pedigree of type 2 diabetes complicated with interstitial lung disease - Zhang, Qinghua; Wang, Yan; Tian, Chang; Yu, Jinyan; Li, Yanlei; Yang, Junling (Frontiers in Endocrinology, 2023)
Purpose: Diabetes mellitus is a systemic metabolic disorder which may target the lungs and lead to interstitial lung disease. The clinical characteristics and mechanisms of type 2 diabetes mellitus (T2DM) complicated with interstitial lung disease (ILD) has been studied. However, little work has been done to assess genetic contributions to the development of T2DM complicated with ILD. Method: A pedigree of T2DM complicated with ILD was investigated, and the whole genome re-sequencing was performed to identify the genetic variations in the pedigree. According to the literature, the most valuable genetic contributors to the pathogenesis of T2DM complicated with ILD were screened out, and the related cellular functional experiments were also performed. Results: A large number of SNPs, InDels, SVs and CNVs were identified in eight subjects including two diabetic patients with ILD, two diabetic patients without ILD, and four healthy subjects from the pedigree. After data analysis according to the literature, MUC5B SNP rs2943512 (A > C) was considered to be an important potentially pathogenic gene mutation associated with the pathogenesis of ILD in T2DM patients. In vitro experiments showed that the expression of MUC5B in BEAS-2B cells was significantly up-regulated by high glucose stimulation, accompanied by the activation of ERK1/2 and the increase of IL-1β and IL-6. When silencing MUC5B by RNA interference, the levels of p-ERK1/2 as well as IL-1β and IL-6 in BEAS-2B cells were all significantly decreased. Conclusion: The identification of these genetic variants in the pedigree enriches our understanding of the potential genetic contributions to T2DM complicated with ILD. MUC5B SNP rs2943512 (A > C) or the up-regulated MUC5B in bronchial epithelial cells may be an important factor in promoting ILD inT2DM patients, laying a foundation for future exploration about the pathogenesis of T2DM complicated with ILD.